The Association Between Psoriasis and Risk of Cardiovascular Disease: A Mendelian Randomization Analysis - Gao, Ning; Kong, Minjian; Li, Xuebiao; Zhu, Xian; Wei, Dongdong; Ni, Ming; Wang, Yifan; Hong, Ze; Dong, Aiqiang (Frontiers in Immunology, 2022)
Background: A large number of observational studies showed that patients with psoriasis have a higher risk of cardiovascular disease (CVD), but most studies did not fully adjust confounding factors, so it is not clear whether the risk of CVD is directly attributed to psoriasis. We used Mendelian randomization (MR) to comprehensively evaluate the potential causal relationship between psoriasis and CVD. Methods: We used genetic instruments from the genome-wide association study (GWAS) of European descent for psoriasis to investigate the relationship with CVD. Inverse variance-weighted (IVW) MR analyses were used for the primary analysis. And a variety of other methods were used to replicate the analysis. Results: The fixed-effects IVW method indicated that genetic susceptibility to psoriasis was associated with a higher risk of Heart Failure (HF) (OR=1.04; 95%CI, (1.01-1.06), P=2.72E-03), Atrial Fibrillation (AF) (OR=1.04; 95%CI, (1.02-1.07), P=3.27E-04), Miocardial Infarction (MI) (OR=1.07; 95%CI, (1.01-1.12), P=0.01), Valvular Heart Disease (VHD) (OR=1.001; 95%CI, (1.000-1.002), P=1.85E-03) and Large Artery Stroke (LAS) (OR=1.11; 95%CI, (1.05-1.18), P=5.37E-04), but not with the other two subtypes of Ischemic Stroke (IS) (Cardioembolic Stroke (CES) (OR=1.03; 95%CI, (0.98-1.07), P=0.27) and Small Vessel Stroke (SVS) (OR=1.00; 95%CI, (0.95-1.07), P=0.88)). Sensitivity analysis found weak evidence of horizontal diversity and heterogeneity to ensure the stability of the results. Conclusion: Our study provided evidence for a potential causal link between psoriasis and cardiovascular disease. These findings facilitate early monitoring of cardiovascular risk in patients with psoriasis and encourage active management of cardiovascular risk factors.